2012
DOI: 10.1177/1932202x12451439
|View full text |Cite
|
Sign up to set email alerts
|

Schoolwide Mathematics Achievement Within the Gifted Cluster Grouping Model

Abstract: An increasing number of schools are implementing gifted cluster grouping models as a cost-effective way to provide gifted services. This study is an example of comparative action research in the form of a quantitative case study that focused on mathematic achievement for nongifted students in a district that incorporated a schoolwide cluster grouping model. Although previous research found that gifted students performed better in the cluster setting, this study sought to determine the effects of the cluster mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
2
17
0
1
Order By: Relevance
“…In the end, researchers found no evidence to show that school-wide cluster grouping benefited or harmed academic achievement in the area of reading, but displayed positive results in math the year after implementation, suggesting that it may take more than one year for the benefits of cluster grouping to become apparent. The results of Matthews et al (2013) align with the findings of Brulles et al (2012) which concluded that school-wide cluster grouping did not have any lasting benefits or harm to students' academic achievement. Matthews et al (2013) found these results in reading, whereas Brulles et al (2012) found them in mathematics, which contradicts Matthews et al's (2013) research that school-wide cluster grouping increases students' math achievement.…”
Section: Between-class Ability Groupingsupporting
confidence: 78%
See 4 more Smart Citations
“…In the end, researchers found no evidence to show that school-wide cluster grouping benefited or harmed academic achievement in the area of reading, but displayed positive results in math the year after implementation, suggesting that it may take more than one year for the benefits of cluster grouping to become apparent. The results of Matthews et al (2013) align with the findings of Brulles et al (2012) which concluded that school-wide cluster grouping did not have any lasting benefits or harm to students' academic achievement. Matthews et al (2013) found these results in reading, whereas Brulles et al (2012) found them in mathematics, which contradicts Matthews et al's (2013) research that school-wide cluster grouping increases students' math achievement.…”
Section: Between-class Ability Groupingsupporting
confidence: 78%
“…Researchers have studied different styles of between-class ability grouping such as multilevel classes (Gentry & MacDougall, 2009;Kulik & Kulik, 1992;Tieso, 2003), cross-grade grouping (Kulik & Kulik, 1992;Tieso, 2003), school-wide cluster grouping (Brulles, Peters, & Saunders, 2012;Gentry & MacDougall, 2009;Matthews et al, 2009), total-school cluster grouping (Gentry & Owen, 1999;Gentry & MacDougall, 2009), and tracking (Gentry & MacDougall, 2009;Matthews et al, 2009;Worthy, 2010).…”
Section: Between-class Ability Groupingmentioning
confidence: 99%
See 3 more Smart Citations